Group therapy for alcohol addiction treatment before liver transplantation reduces post-transplant alcohol relapse: preliminary results of a monocentric retrospective study. (March 2023) - Costa, E. Garlatti; Colussi, G.; Meneguzzi, C.; Grazioli, S.; Tonizzo, M.
Abstract : Introduction: Long-term survival of patients with end-stage alcoholic liver disease is excellent after liver transplantation (LT), but the predisposition to alcohol relapse (AR) in these patients can reduce such a beneficial effect. Aim: To assess whether participation in group therapy for alcohol addiction treatment before LT can reduce post-transplant AR. Materials: Clinical and social informations of 16 consecutive liver transplanted patients (age 57±8 years, 3 females) were collected from January 2019 to December 2022 and patients were followed for median 12.5 months (interquartile range 3.8-25.6). Difference between participants and not participants in group therapy was assessed by restricted mean event time analysis. Alcohol addiction was diagnosed by Diagnostic and Statistical Manual of Mental Health-IV criteria and alcohol abstinence was assessed by patient or caregiver interview and confirmed by urinary sample analysis. Results: AR was observed in 4 patients (25%), 3 patients after 12 months from LT and earlier in 1 patient. Two patients among those with AR became heavy drinkers. Eight patients participated in group therapy before LT, whereas the others refused it. In participants in group therapy, no AR was observed, whereas in not participants AR was observed in 4/8 patients (0% vs 50%, respectively, p=0.077). Not significant differences in age, sex, marital status, caregiver presence, alcohol addiction severity, 6-month alcohol abstinence, and MELD score were observed before LT between participants and not-participants in group therapy. The mean time to AR in the not participants in group therapy was 17.6 months (95% confidence interval 8.6-27.5), whereas the mean observation time of participants without AR was 34 months (p=0.011). Conclusions: This study shows that participation in group therapy for alcohol addiction treatment before LT can reduce post-transplant AR. This preliminary result justifies the design of confirmatory prospective clinical trials.